2015
DOI: 10.1177/0009922815591887
|View full text |Cite
|
Sign up to set email alerts
|

Report of Sugar-Sweetened Beverages Offered in Pennsylvania Childcare Centers

Abstract: The study objective was to quantify sugar-sweetened beverage (SSB) offerings to children in Pennsylvania (PA) childcare centers and determine whether this information is communicated to parents. In October 2014, a SurveyMonkey link was sent to 4461 PA childcare centers. The 518 respondents represented 88% of PA counties. 279 centers (54%) serve SSBs. 330 (65%) of childcare centers provide parents a report of their child's daily intake. Of 185 centers serving SSBs and providing a daily intake report, 91% includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…New York City has a child care beverage policy similar to California, except that flavored milk and juice are not addressed. Compared with our 2016 California survey, in a 2010 study, adherence to the New York City policy was higher for milk (80%), and lower for SSBs (70%) and water (56%) (15). However, the New York City study only included centers, 90% of which participated in CACFP.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…New York City has a child care beverage policy similar to California, except that flavored milk and juice are not addressed. Compared with our 2016 California survey, in a 2010 study, adherence to the New York City policy was higher for milk (80%), and lower for SSBs (70%) and water (56%) (15). However, the New York City study only included centers, 90% of which participated in CACFP.…”
Section: Discussionmentioning
confidence: 60%
“…As adherence to state and federal regulations regarding allowable beverages in California child care sites continues to improve, consumption of unhealthy beverages is likely to decrease, there being a strong and direct relationship between beverages served at child care sites and children's beverage consumption (15). This may result both in long-term health care cost savings through preventing childhood obesity and possible cost savings for the child care site.…”
Section: April 2020mentioning
confidence: 99%
“…For example, a recent study in Pennsylvania found that more than half of child care centers surveyed offered sugar-sweetened beverages to children. 22 Although sites did not report insufficient training as a barrier to implementing the new CACFP standards, stakeholders emphasized the need to help providers understand not only the content, but also how to operationalize the standards, expressing a concern that some providers might Respondents were allowed to select multiple answer options so percentages do not add up to 100% across a row. a Includes write-in responses.…”
mentioning
confidence: 99%
“… 11 It is important to note that the response rate reported here is similar to those reported in previous studies that surveyed center-based child care programs. Lutzkanin, Myers, Schaefer, and Sekhar (2016) and Joshi, Ocanto, Jacobs, and Bhoopathi (2016) report response rates of 11.6% and 17.0%, respectively, in web-based surveys of center-based directors. Interestingly, Schaack and Le (2017) combine e-mail recruitment with a web-based survey, along with a $200 financial incentive, and achieve only a 23.6% response rate.…”
mentioning
confidence: 99%